Analisis Kualitas Produk Skincare HN - Lisa Julianti; Siti Sutihat; Syamsul Hidayat (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The concept of beauty currently circulating in society is having white skin. There are a number of whitening products that contain dangerous ingredients such as mercury and hydroquinone that are not permitted by BPOM. Beauty products are currently being discussed, not only because of the products that are flooding the market, but also because of the impact of using these products. This research aims to analyze the quality of HN skincare products based on student perceptions in a business context. This research method uses descriptive quantitative. The sample used was 181 Bina Bangsa University students who were willing to become respondents and were taken randomly. The results of this research show that as many as 8 questions significantly show that Bina Bangsa University students do not use and are less interested in using HN products on the grounds that they are dangerous.